Volume Depletion versus Dehydration: How Understanding the Difference Can Guide Therapy - Bhave, Gautam (2011)
Using a case of hyperglycemic hypertonic nonketosis we examine the changing composition of body fluid spaces to explore the distinction between dehydration with hypertonicity and volume depletion. These terms have specific meaning and their proper use guides therapy when pathophysiology disturbs the composition of various body fluid compartments.